Development of Total Lymphoid Irradiation (TLI)-Dedicated Shielding and Image-Guided System and Dose Evaluation Using 3D-Printed Rat Phantom - Choi, Dong Hyeok; Ahn, So Hyun; Park, Kwangwoo; Choi, Sang Hyun; Kim, Jin Sung (Frontiers in Veterinary Science, 2022)
Purpose: The purpose of this study is to propose a technique for delivering accurate dose in an image-guided system by developing an experimental setup optimized for TLI in rat lung transplantation. Materials and Methods: In this study, a position-controlled shielding system was developed, and the dose was quantitatively evaluated using a 3D rat phantom and EBT3 film. In addition, we made our own image-guided system that allows the position of the rat and the shielding system to be confirmed during TLI. Results: As a result of using the position-controlled shielding system, it was found that the doses to the head and lungs were reduced by 93.1% and 87.4%, respectively, of the prescribed doses. In addition, it was shown that the position of the shielding system can be easily confirmed by using the image guidance system. Conclusion: A shielding apparatus that can control dose delivery according to the size of the rat can optimize the dose for TLI in rat lung transplantation.